2001
DOI: 10.1046/j.1467-789x.2001.00033.x
|View full text |Cite
|
Sign up to set email alerts
|

The importance of physical activity in the prevention of overweight and obesity in childhood: a review and an opinion

Abstract: The prevalence of childhood obesity is increasing and there are a number of theoretical reasons as to why intervention may be more effective in childhood. There are certain risk times for the development of obesity in childhood, which provide a basis for targeted intervention. In addition, tracking data supports the persistence of obesity, at least in later childhood, as well as cardiovascular risk factors. Physical activity is the discretionary component of energy expenditure and there is evidence that fallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
146
2
10

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(161 citation statements)
references
References 136 publications
(126 reference statements)
3
146
2
10
Order By: Relevance
“…Overweight and obesity in children are linked to the image that parents reflect and behaviour they try to inculcate in their children, in particular, food habits and physical exercise [25] [46]. In our study, physical activity of the mother or father was not associated to the children's overweight or obesity.…”
Section: Discussioncontrasting
confidence: 51%
“…Overweight and obesity in children are linked to the image that parents reflect and behaviour they try to inculcate in their children, in particular, food habits and physical exercise [25] [46]. In our study, physical activity of the mother or father was not associated to the children's overweight or obesity.…”
Section: Discussioncontrasting
confidence: 51%
“…Physical inactivity poses serious health risks for children and most of the chronic diseases observed at later ages have started to emerge during childhood periods (The Ministry of Health, 2014). PA during the childhood, on the other hand, is associated with many health benefits, including improving cardiovascular health (Janssen & LeBlanc, 2010;Timmons, et al, 2012; The Ministry of Health, 2014), better cognitive functioning (Sibley & Etnier, 2003;Timmons, et al, 2012), bone and skeletal health (Gunter, et al, 2012;Timmons, et al, 2012), motor skill development and psychosocial health (Timmons, et al, 2012), reducing obesity (Trost, et al, 2001;Steinbeck, 2001; The Ministry of Health, 2014) and lower symptoms of depression and anxiety (Strong, et al, 2005;Motl, et al, 2004;The Ministry of Health, 2014). Likelihood that development of healthy lifestyles later in adulthood is contributed by PA during childhood (Hallal, et al, 2006), including early childhood (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Although the longitudinal relationship between physical activity level and obesity has been questioned, 4 this association has been documented in a number of cross-sectional studies. [5][6][7] Recently, Besson et al 8 using data obtained from adults in nine European countries included in the EPIC (European Prospective Investigation into Cancer and nutrition) study, showed a strong inverse relationship between total physical activity and body mass index (BMI), independent of age, gender and country, as well as other potential confounding factors, including energy intake.…”
Section: Introductionmentioning
confidence: 99%